Targeting therapy-resistant lung cancer stem cells via disruption of the AKT/TSPYL5/PTEN positive-feedback loop - In-Gyu Kim (Nature Portfolio, 2021)
In order to assist the development of cancer stem cell (CSC) therapy, Kim et al identified testis-specific Y-like protein 5 (TSPYL5) as an upstream regulator of CSC-associated genes in non-small cell lung cancer cells. They demonstrated in cancer cell lines and in vivo that TSPYL5 activity is dependent on AKT signalling and that disruption of TSPYL5 signalling could serve as a potential strategy to tackle therapy-resistant cancers.